Airborne measurements of a polar low over the Norwegian Sea - Yoshio Asuma; Yoko Fukuda; Katsuhiro Kikuchi; Masaki Shiobara; Makoto Wada; G.W.K. Moore (Antarctic Record, 2002)
We will report an airborne measurement of a polar low over the Norwegian Sea on 9 March 1998 during the Arctic Airborne Measurement Program 1998 (AAMP 98). Global objective analysis suggests that the low formed due to an interaction between an upper level potential vorticity anomaly and a low-level baroclinic zone. Seven constant height transects in the zonal direction were made in the convective line clouds associated with the polar low. A strong horizontal temperature gradient in the zonal direction was observed in the lower boundary layer. Gale force northerly winds, in thermal wind balance with this baroclinity, were also observed in the lower atmosphere.